A chronology of alluvial fan response to Late Quaternary sea level and climate change, Crete. Issue 2 (September 2016) - Pope, Richard J.J.; Candy, Ian; Skourtsos, Emmanuel
Abstract: To better understand how fluvial systems respond to late Quaternary climatic forcing OSL and U-series dating was applied to stratigraphically significant sedimentary units within a small (<6.5 km 2 ) alluvial fan system (the Sphakia fan) in southwest Crete. The resultant chronology (comprising 32 OSL and U-series ages) makes Sphakia fan one of the best dated systems in the Mediterranean and suggests that Cretan fans responded to climate in two ways. First, during the transitions between Marine Isotope Stage (MIS) 5a/4 and MIS 2/1 Sphakia fan was characterised by significant entrenchment and distal shift in the zone of deposition. It is proposed that the phases of entrenchment were driven by sea level induced base level fall during MIS 5a/4 and landscape stabilisation during the onset of the current interglacial (MIS 2/1). Second, with the exception of these two entrenchment episodes fan alluviation occurred across the entire last interglacial/glacial cycle in all climatic settings i.e. interglacials, interstadials and stadials. It is likely that the topographic setting of the catchment supplying sediment to Sphakia fan maintained high sediment transfer rates during most climatic settings enabling fan aggradation to occur except during major climatic driven transitions i.e. major sea level fall and postglacial vegetation development.